Small presses and literary/artistic collaboration in the U.S. after 1945: The examples of The Black Mountain Review, Jargon Press, and Granary Books - Barbara Montefalcone (IdeAs)
The early 20th century European avant-garde movements have extensively shown the connection existing between the activity of independent publishers and the practice of literary/artistic collaboration. Such works as La Prose du Transsibérien et de la petite Jeanne de France (Blaise Cendrars and Sonia Delaunay, 1913) or Facile (Paul Eluard and Man Ray, 1935), would have never been published if the little review Les hommes nouveaux or the small publisher G.L.M had not acted as facilitators to allow those works to reach an audience.The artistic and publishing context of post-war America, though different from that of pre and post World War I Europe, presents interesting parallels concerning the role of small presses in encouraging the activity of collaboration between artists and writers. By exploring the work of daring editors and publishers as Robert Creeley (The Black Mountain Review), Jonathan Williams (Jargon press), and more recently, of Steve Clay (Granary Books) it is possible to see how, during the latter part of the 20th century, American avant-garde poetry found a way to circulate and to express its unique voice by its association - and most of the time by its collaboration - with the visual arts. In the 1950s Creeley insisted to match, in the seven issues of The Black Mountain Review that he edited, the most innovative poetry of the time with the reproductions of works by contemporary artists, and this in a way that was totally unique at the time. Jonathan Williams, through his Jargon series of well-crafted books, echoed Creeley’s work and put an even stronger emphasis on the activity of collaboration between the artists and the writers that he chose to publish. In more recent times (1980) Steve Clay took on the movement started years earlier by Creeley and Williams and, by establishing his publishing house known as Granary Book, began publishing a long series of collaborative works where the specificity of the writing is directly embodied in the material aspect of the book.